Parliamentary Opinions. - Malamut, Michael; Lochrie, James; Schilansky, Mark; Stackpole, John; Sylvester, Nancy (Parliamentary Journal, 2009)
Part of a special issue on “e-meetings.” The writers offer their opinions on two recent occurrences relevant to the issue of e-meetings. They discuss these events, which they call “2009–538: Adequate Bylaws Authorization for Email Notice” and “2009–539: President Fails to Call the Meeting – Vice President Does.” They offer their opinions as to whether these occurrences were handled effectively.